PENGEMBANGAN MEDIA TRUTH or DARE SPIN WHEEL PADA PEMBELAJARAN IPA TERHADAP EFEK POTENSAL SISWA KELAS IV SEKOLAH DASAR - Dona, Ignasius; Oktavia, Maharani; Ayurachmawati, Puji (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to create Truth or Dare Spin Wheel media at Class IV Elementary School on Science Learning with validity, practicality and potential effects. The method used by this researcher is research and development with the ADDIE model which includes 5 stages, namely Analyze, Design, Development, Implementation and Evaluation. The subjects of this research were class IV students at SD Negeri 007 Palembang. The results of this research show that the Truth or Dare Spin Wheel media at fourth grade elementary school on science learning is in the very valid category with 89.3% which is combined from the three validators. Practicality results can be seen from the results of the questionnaire for the entire student trial, the test is 91.4%, so the Truth or Dare Spin Wheel media is concluded to be very practical to be used and the potential effects obtained from the post test results through the use of Truth or Dare Spin Wheel media on science learning at class IV SD was stated to have a very potential effect with 83.4%. Based on the results of research through the validation stage, student questionnaires and post-test results of students using Truth or Dare media at Class IV Elementary Science Learning, it was stated suitable to be used to increase the potential effect of elementary school students.